Lateralidade no uso das mãos durante a alimentação por Brachyteles hypoxanthus em ambientes natural - Slomp, Daniel Vilasboas (2016)
Over the last decades, it has become clear that behavioral lateralization is not restricted to humans. The most evident manifestation of laterality in humans is the prevalence of handedness, the dominant use of the right hand, which is related to the development of the left cerebral hemisphere. Nonhuman primates express varying degrees of laterality, but exhibit a population-level handedness less intense than humans. There is a strong debate about the origin and evolution of primate handedness. This debate focuses on two main hypothesis. The Postural Origins Theory (POT) states that arboreal primates exhibit a left hand preference, whereas terrestrial primates exhibit a right hand preference. The Task Complexity Theory (TCT) states that the complexity of the task modulates hand preference in primates. While low-level tasks do not require hand specialization, high-level tasks elicit hand preference. We studied the handedness of members of a wild population of northern muriquis during a simple unimanual and bimanual low-level task – the simple reach of food items – in their three-dimensional arboreal habitat. The aim of the study was to evaluate whether northern muriquis exhibit a left hand preference, as predicted by the POT for arboreal primates, or a lack of hand preference, as predicted by the TCT for low-level tasks. The muriquis showed a population-level left hand bias when performing the low complexity task. There were no sex differences in handedness. The muriquis exhibited stronger handedness when engaged in bimanual than in unimanual feeding activity. We suggest that the release of the hands from the postural demands when individuals are hanging from their tails and feet favors the expression of laterality in muriquis. Therefore, postural stability in the arboreal environment seems to modulate the degree of handedness in northern muriquis. We compare these results with the pattern observed in other nonhuman primates and discuss them in light of the factors associated with handedness in humans. We suggest that studies in both arboreal and terrestrial environments are necessary to assess the implications of these environmental differences for the origin of handedness in the first hominids.